A proposed model of value co-creation through multi-stakeholder collaboration in domestic product development - Permatasari, Anggraeni; Dhewanto, Wawan; Dellyana, Dina (Business: Theory and Practice, 2021)
This study illustrates the collaborative value co-creation process that involves multi-stakeholders in developing domestic products and services design in Indonesia. Although the value co-creation process performed effectively, the new product is still experiencing obstacles in term of commercialization and sustainability. The purpose of this research is to construct a model to encourage the process of value co-creation in the commercialization phase of domestic products. The qualitative method with a single case study approach is conducted in this research. Data collected with in-depth interviews, observations and archival. The informants are representatives of stakeholders that interact and participate in the IKKON program. Data analyzed with DART model (Dialogue, Access, Risk Assessment and Transparency) to examine the process of value co-creation in the IKKON program. This approach constructs an analysis that involves stakeholder’s experience during the value co-creation process as a basis for innovation. The results showed with collaboration; stakeholders could learn from each other to understand the needs. The collaboration with multi-stakeholder will increase the values of the product by combining local and public needs. The finding proposed a collaborative model to optimizing domestic product in terms of commercialization. This research enlarges a practical perspective in managing value co-creation and decision making.